If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x * x) + 3 = x(x + 1) + 2 + 2 Multiply x * x (x2) + 3 = x(x + 1) + 2 + 2 x2 + 3 = x(x + 1) + 2 + 2 Reorder the terms: 3 + x2 = x(x + 1) + 2 + 2 Reorder the terms: 3 + x2 = x(1 + x) + 2 + 2 3 + x2 = (1 * x + x * x) + 2 + 2 3 + x2 = (1x + x2) + 2 + 2 Reorder the terms: 3 + x2 = 2 + 2 + 1x + x2 Combine like terms: 2 + 2 = 4 3 + x2 = 4 + 1x + x2 Add '-1x2' to each side of the equation. 3 + x2 + -1x2 = 4 + 1x + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 3 + 0 = 4 + 1x + x2 + -1x2 3 = 4 + 1x + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 3 = 4 + 1x + 0 3 = 4 + 1x Solving 3 = 4 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 3 + -1x = 4 + 1x + -1x Combine like terms: 1x + -1x = 0 3 + -1x = 4 + 0 3 + -1x = 4 Add '-3' to each side of the equation. 3 + -3 + -1x = 4 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 4 + -3 -1x = 4 + -3 Combine like terms: 4 + -3 = 1 -1x = 1 Divide each side by '-1'. x = -1 Simplifying x = -1
| 1234671234=2x+5y+18e+757547g | | x^3-8x^2+45=0 | | 19v^2+35v=0 | | 33=1x+3+2x | | 2x-(3x+5)/4=-0.25x-1 | | j^2+46j=0 | | 2cotx+3=1 | | 2d^2+7d-15=0 | | 2x-(3x+5)/4=-1/4x-1 | | -1-4p=39 | | p^2-13p=0 | | -9(-5+a)=-90 | | n^2+24n+23=0 | | (2x-3)/4=1/2+x | | 3x(2)+3x=x(2)+5+5x | | (-7x)(2x^2)= | | s^2-7s+6=0 | | (3x)(9y)(4z)= | | p=3x+2 | | x(7x+9)=2x^2-14x+10 | | x+4+x+4+x+4=30 | | (5x+3)(8x-3)=0 | | (2x)(6y)= | | 7x-(4x+5)=4x-18 | | 2x+1+x+x+5=30 | | 2=in(x+9) | | 9x-5=85-x | | 3+4n=8n+7 | | 14r+(3q-10r+2q)= | | -4+4(2-5x)=-9 | | x^4+4x^3+5x^4=0 | | 5x-2(x+4)=10 |